2004
DOI: 10.1097/00004836-200408000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Irritable Bowel Syndrome

Abstract: Men with irritable bowel syndrome exhibit less male characteristics and it remains to be determined whether this is cause or effect. Whatever the explanation, this study adds another dimension to the role of gender in functional gastrointestinal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 10 publications
0
35
1
Order By: Relevance
“…However, IBS considerably reduces quality of life to the same degree of impairment as major chronic diseases, including diabetes, congestive heart failure, renal insufficiency and hepatic cirrhosis (17)(18)(19)(20)(21). Besides the increased morbidity caused by IBS, the syndrome is an economic burden to society in varying forms, for example by increasing the incidence of sick leave and the over-consumption of healthcare resources (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, IBS considerably reduces quality of life to the same degree of impairment as major chronic diseases, including diabetes, congestive heart failure, renal insufficiency and hepatic cirrhosis (17)(18)(19)(20)(21). Besides the increased morbidity caused by IBS, the syndrome is an economic burden to society in varying forms, for example by increasing the incidence of sick leave and the over-consumption of healthcare resources (1).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon might be interpreted as a defect in the system that regulates testosterone functions. Previous studies have suggested that male sex hormones might protect against IBS [5, 11]. However, the previously reported altered sex hormones were LH and testosterone, not SHBG.…”
Section: Discussionmentioning
confidence: 93%
“…Most explanations of IBS have focused on the concept that women might be more susceptible, in some way, but little attention has been given to the possibility that there may be a protective effect for males [11]. Moreover, there are few reports regarding the role of sex hormones in male patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Other studies have found that men with IBS have more nurturing traits and reduction in the male-trait score. 18,19 Psychological Factor and Abuse A history of abuse predisposes patients to IBS. In addition to having a history of abuse of varying types; emotional, sexual, or physical and/or a history of stressful life events, social stress or anxiety and having a maladaptive coping style, affect the severity and clinical course of IBS.…”
Section: Gender and Hormonesmentioning
confidence: 99%